2017
DOI: 10.1007/s10803-016-2985-0
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and Non-Linguistic Semantic Processing in Individuals with Autism Spectrum Disorders: An ERP Study

Abstract: Individuals with autism spectrum disorders (ASD) experience difficulties with language, particularly higher-level functions like semantic integration. Yet some studies indicate that semantic processing of non-linguistic stimuli is not impaired, suggesting a language-specific deficit in semantic processing. Using a semantic priming task, we compared event-related potentials (ERPs) in response to lexico-semantic processing (written words) and visuo-semantic processing (pictures) in adults with ASD and adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 56 publications
9
54
2
Order By: Relevance
“…Such bottom-up processing could also explain the reduced N400 effects at the anomalous final panels, in which semantic processing of anomalous stimuli may rely on the same bottom-up strategies as other units in the sequence. This would also complement our recent findings of a more bottom-up, post-lexical integration strategy of semantic processing in ASD compared to a more top-down, prediction-based strategy in TD individuals (Coderre et al, 2017).…”
Section: Narrative Comprehension In Asdsupporting
confidence: 76%
See 2 more Smart Citations
“…Such bottom-up processing could also explain the reduced N400 effects at the anomalous final panels, in which semantic processing of anomalous stimuli may rely on the same bottom-up strategies as other units in the sequence. This would also complement our recent findings of a more bottom-up, post-lexical integration strategy of semantic processing in ASD compared to a more top-down, prediction-based strategy in TD individuals (Coderre et al, 2017).…”
Section: Narrative Comprehension In Asdsupporting
confidence: 76%
“…related to language ability, but rather may represent more global impairments in understanding narrative sequences. We conclude, albeit speculatively, that prior evidence of an advantage of visuo-semantic over lexico-semantic processing in individuals with ASD (Coderre et al, 2017;Kamio & Toichi, 2000;Sahyoun et al, 2009) may not necessarily completely overcome more general difficulties with narrative comprehension in these individuals.…”
Section: Narrative Comprehension In Asdmentioning
confidence: 70%
See 1 more Smart Citation
“…This sample size was defined a-priori to match that used (for each group) in Van Berkum et al (2008), and it is comparable to or exceeds the sample sizes of previous studies that have used EEG to study language in autism (e.g. Coderre, Chernenok, Gordon, & Ledoux, 2017;Korpilahti et al, 2007;Pijnacker, Geurts, Van Lambalgen, Buitelaar, & Hagoort, 2010;Lartseva, Dijkstra Kan, & Buitelaar, 2014). Nevertheless, post-hoc power calculations showed an estimated power of approximately 38% to detect a significant 4-way interaction.…”
Section: Experiments 2 Methodsmentioning
confidence: 99%
“…Recent work has used this approach to assess covert cognitive abilities in non-communicative populations (see a recent review by Harrison and Connolly, 2013). In particular, language processing has been studied using EEG including in patients with disorder of consciousness (Hinterberger et al, 2005;Kotchoubey et al, 2005), schizophrenia (Mathalon et al, 2002;Sharma et al, 2017), and autistic individuals (Coderre et al, 2017;Pijnacker et al, 2010;Wang et al, 2017). However, in these cases, EEG research has focused on the population-level, with minimal data reported on an individual-participant basis.…”
Section: Introductionmentioning
confidence: 99%